Impact of post-operative hip-knee-ankle angle changes on functional outcome of total knee arthroplasty: a prospective longitudinal study - Palit, Sukanya; Roy, Tapobrata Guha (International Journal of Research in Orthopaedics, 2022)
Background: Coronal malalignment as residual varus may have deleterious effects on functional outcomes of total knee arthroplasty. This study aimed at highlighting the impact of postoperative hip-knee-ankle (HKA) angle changes on the functional outcome of total knee arthroplasty. Methods: 689 total knee arthroplasty (TKA) knees (from 386 patients) with varus postoperative HKA angle were included. HKA angle was measured on standing orthoscanograms. The knees were divided into 5 subgroups according to postoperative HKA angle as: neutral (0±3.0 degrees); mild (3.1-6.0 degrees); moderate (6.1-10.00 degrees); severe (10.1-5.0 degrees); very severe (>15.0 degrees). Functional outcome of TKA in these subgroups was observed by knee society score (KSS), knee society pain score (KSS-P), Oxford knee score (OKS), lower extremity functional scale (LEFS) at 6 months, 1 year, 2 years, 3 years. Statistical analysis was done by statistical package for social sciences (SPSS) version 16; Spearman’s correlation coefficient and Kruskall Wallis test was used to compare the functional outcome of TKA between COHORTs. Results: 69 knees were present in the mild varus cohort (mean: -1.92), 223 knees in the moderate varus COHORT (mean: -4.77), 260 knees in the moderate varus COHORT (mean: -7.86), 121 knees in the severe varus COHORT (mean: -11.60) and 16 knees in the very severe varus COHORT (mean: -16.54). Mild to moderate varus knees were maximum, but no significant difference in functional outcome between these COHORTs was found by correlation analysis and Kruskall Wallis test. Conclusions: Changes in postoperative HKA angle (coronal alignment) has no significant impact on functional outcome of TKA.